2022
DOI: 10.3390/foods11121785
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and In Vitro Analyses of Angiotensin-I Converting Enzyme Inhibitory and Antioxidant Activities of Enzymatic Protein Hydrolysates from Taiwan Mackerel (Scomber australasicus) Steaming Juice

Abstract: Mackerel (Scomber australasicus) steaming juice (MSJ) can be a good source of proteins. However, it is often treated as food waste during the canning process. The objective of this study was to investigate the Angiotensin-I converting enzyme (ACE-I) inhibitory and antioxidant activities from MSJ hydrolysates using in silico and in vitro approaches. Proteins extracted from MSJ were identified by proteomic techniques, followed by sulfate polyacrylamide gel electrophoresis (SDS-PAGE), in-gel digestion, tandem mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…According to previous studies, a varying degree of protein breakdown and the duration of hydrolysis could result in different SDS‐PAGE profiles of recovered FPHs. [ 18 , 19 ] The protein hydrolysates of the Taiwan mackerel ( Scomber australasicus ) steaming juice (MSJ) were found to have different bands of different molecular weights between 28 and 180 kDa in SDS‐Page analysis by Panjaitan et al., [ 20 ] in which the protein was mostly above 63 kDa in defatted MSJ, while mackerel muscle proteins were present in bold bands around 35, 48, and 100 kDa. Qara and Habibi, [ 19 ] reported that hydrolysates obtained by Alcalase and Neutrase from Kilka ( Clupeonella cultriventris Caspian ) indicated higher levels of peptides with MW below 30 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, a varying degree of protein breakdown and the duration of hydrolysis could result in different SDS‐PAGE profiles of recovered FPHs. [ 18 , 19 ] The protein hydrolysates of the Taiwan mackerel ( Scomber australasicus ) steaming juice (MSJ) were found to have different bands of different molecular weights between 28 and 180 kDa in SDS‐Page analysis by Panjaitan et al., [ 20 ] in which the protein was mostly above 63 kDa in defatted MSJ, while mackerel muscle proteins were present in bold bands around 35, 48, and 100 kDa. Qara and Habibi, [ 19 ] reported that hydrolysates obtained by Alcalase and Neutrase from Kilka ( Clupeonella cultriventris Caspian ) indicated higher levels of peptides with MW below 30 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…The FDA, specifically the Centre for Veterinary Medicine (CVM), is responsible for the regulation of animal food products and has procedures to approve food additives for use, which apply to any product unless it is generally recognized as safe for that intended use (i.e., forages, grains, and most mineral and vitamins). [ 48 ] If an FPH claims: “to cure, treat, prevent, or mitigate disease, the product should be considered a “new animal drug”. Pet food, including pet treats but not pet supplements, falls under the AAFCO and these are regulated at federal and state levels.…”
Section: Legislation and Regulationsmentioning
confidence: 99%
“…Pet food, including pet treats but not pet supplements, falls under the AAFCO and these are regulated at federal and state levels. [ 48 ] FPHs marketed as nutritional supplements must adhere to set guidelines. They must, for example, state a known need for each nutrient ingredient represented to be in the product.…”
Section: Legislation and Regulationsmentioning
confidence: 99%
See 1 more Smart Citation